2016
DOI: 10.15666/aeer/1404_343356
|View full text |Cite
|
Sign up to set email alerts
|

Soil Respiration Behaviour in a Mediterranean Aleppo Pine Forest in North Tunisia

Abstract: Abstract.Little is known about the relationship between soil respiration and biophysical factors in the Tunisian Aleppo pine forest. We conducted our studies in two adjacent forests in Djebel Mansour region with the same micrometeorological conditions, but they differed in soil proprieties. The main goal of this research was to quantify soil respiration and its seasonal variations under two different soil characteristics. Soil respiration measurements were performed between Mai 2008 and July 2009. The magnitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Quercus suber L. covers 70,000 ha on the northern part of the country where mean annual precipitation is 800 mm, varying between 700 mm and 1500 mm, and mean temperature is 16 • C [21]. Pinus halepensis Miller covers 361,000 ha in the central part of the country where mean annual precipitation is 400 mm [22]. Mediterranean shrublands cover 328,000 ha and they are composed of Arbutus unedo L., Erica arborea L. Cistus spp.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Quercus suber L. covers 70,000 ha on the northern part of the country where mean annual precipitation is 800 mm, varying between 700 mm and 1500 mm, and mean temperature is 16 • C [21]. Pinus halepensis Miller covers 361,000 ha in the central part of the country where mean annual precipitation is 400 mm [22]. Mediterranean shrublands cover 328,000 ha and they are composed of Arbutus unedo L., Erica arborea L. Cistus spp.…”
Section: Study Areamentioning
confidence: 99%
“…In Tunisia, fuel moisture conditions can be regionally variable in the forested wettest northern part of the country according to the climate gradient and topographical features [21,30,31]. In addition, shallow-rooted shrubland species and the herbaceous litter fuel at the surface layer comprise a large part of natural vegetation, and may be even more susceptible to frequent summer droughts [22,23,32]. Over the whole country, long-term drought reconstructions that are based on tree-rings revealed that recent decades appear as among the driest [33], and confirmed recurrent droughts in the studied period.…”
Section: Heat Waves and Fire Events In The Mediterranean Basinmentioning
confidence: 99%
“…Quercus suber L. covers 70,000 ha on the northern part of the country where mean annual precipitation is 800 mm varying between 700 m and 1500 m, and mean temperature is 16 • C [42,43]. Pinus halepensis Miller covers 361,000 ha in the southern part of the country where mean annual precipitation is 400 mm [44]. Mediterranean shrublands cover 328,000 ha and are composed of Arbutus unedo L., Erica arborea L., Cistus spp.…”
Section: Study Areamentioning
confidence: 99%
“…5 a,b). The root respiration and microbial decomposition contributed to the high value of the total ST (Tang et al 2005) and were most common in the growing period of the pine-dominated forest (Rezgui et al 2016). In some pine forests of central California (Carbone et al 2011), the conifer forest of San Rossore (Matteucci et al 2015) and the Tunisian Aleppo pine forest (Rezgui et al 2016) reported that autotrophic SR peaks after the precipitation events.…”
Section: Discussionmentioning
confidence: 98%